Electron capture and ionization processes in high-velocity Cn+, C–Ar and Cn+, C–He collisions. (17th March 2015) - Labaigt, G; Jorge, A; Illescas, C; Béroff, K; Dubois, A; Pons, B; Chabot, M
Abstract: Single-electron and double-electron capture as well as projectile single-ionization and multiple-ionization processes in 125 keV u −1 C –He ( n = 1–5) and C –Ar ( ) collisions have been studied experimentally and theoretically. Helium target single-ionization and double-ionization cross sections are also reported for C –He ( n = 1, 4) collisions in the 100–400 keV u −1 impact energy domain. These results are compared with predictions from the independent atom and electron (IAE) model developed for describing cluster–atom collisions. The ion/atom–atom probabilities required for the IAE simulations have been determined by classical trajectory Monte Carlo (CTMC) and semiclassical atomic orbital close coupling (SCAOCC) calculations for the Ar and He targets, respectively. For comparison, electron capture cross sections were also measured in C–He and C–Ar collisions. In general the agreement between experiment and IAE calculations has been found to be rather good, with the exception of double-electron capture leading to anionic C species.